2017
DOI: 10.1111/cup.12987
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Trichophyton rubrum mimicking blastomycosis in a patient with solid organ transplant

Abstract: We present a case of tissue invasive Trichophyton rubrum (T. rubrum) histologically mimicking blastomycosis in a patient with kidney transplant on chronic immunosuppression. Invasive dermatophyte infections are rare, and present a diagnostic challenge to the dermatopathologist due to atypical clinical and histopathological presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This risk is well known for Fusarium spp. ( Varon et al, 2014 ) and has also been reported in cases of invasive infections by T. rubrum originating from onychomycosis ( Talebi-Liasi and Shinohara, 2017 ).…”
Section: Discussionmentioning
confidence: 80%
“…This risk is well known for Fusarium spp. ( Varon et al, 2014 ) and has also been reported in cases of invasive infections by T. rubrum originating from onychomycosis ( Talebi-Liasi and Shinohara, 2017 ).…”
Section: Discussionmentioning
confidence: 80%
“…Three prior case reports have illustrated T rubrum infection mimicking Blastomyces, with sporelike shapes and pseudobudding on histological findings. [3][4][5] This ambiguity in fungal morphology reaffirms the importance of verifying organism classification through polymerase chain reaction or fungal culture to ensure appropriate therapy and systemic evaluation.…”
Section: Discussionmentioning
confidence: 97%
“…Less than 100 cases of invasive T. rubrum have been reported in the literature since its description by Majocchi et al in 1883. 2 The disease has 4 distinct clinical manifestations: Majocchi granuloma, deep dermatophytosis, disseminated dermatophytosis, and (pseudo)mycetoma (Table I). In the context of immunosuppression and active tinea without systemic antifungal treatment, it is likely that our patient insidiously progressed from superficial to superimposed deep dermatophytosis while being treated for HS.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, pleomorphic features including chlamydoconidium, arthroconidium, pseudobudding, branching hyphae, and broad-based budding have been reported in this population, suggesting a broad variety of possible fungal infections. 2,5,6 Tissue section plane, hyphal orientation, and tissue viability also influence the histological appearance of these structures. 7 Therefore, polymerase chain reaction or culture are often required to determine the causative organism.…”
Section: Discussionmentioning
confidence: 99%